2006
DOI: 10.1189/jlb.0606375
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin I2 analogs inhibit Th1 and Th2 effector cytokine production by CD4 T cells

Abstract: An anti-inflammatory effect of PGI(2) has been suggested by increased inflammation in mice that are deficient in the PGI(2) receptor (IP) or in respiratory syncytial viral- or OVA-induced CD4 T cell-associated responses. To determine the mechanism of the anti-inflammatory effect, we hypothesized that PGI(2) analogs inhibit CD4 T cell effector cytokine production. To test this hypothesis, we activated purified CD4 T cells with anti-CD3 and anti-CD28 antibodies under Th1 and Th2 polarizing conditions for 4 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
84
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 55 publications
(79 reference statements)
3
84
1
Order By: Relevance
“…Independent studies corroborated these findings by demonstrating that iloprost suppresses CCL17, CCL11, lung eosinophil accumulation and the recruitment of CD4+ Th2 to the airways in asthma models [40,41]. PGI 2 counteracts the capacity of T-cells to produce the pro-inflammatory cytokines IL-12, p70, TNF-a, MIP-1a, MCP-1 and IL-6 [42,43]. PGI 2 has also been demonstrated to reduce lipopolysaccharide-induced cytokine production in leukocytes through the inhibition of nuclear factor-kB [44].…”
supporting
confidence: 62%
“…Independent studies corroborated these findings by demonstrating that iloprost suppresses CCL17, CCL11, lung eosinophil accumulation and the recruitment of CD4+ Th2 to the airways in asthma models [40,41]. PGI 2 counteracts the capacity of T-cells to produce the pro-inflammatory cytokines IL-12, p70, TNF-a, MIP-1a, MCP-1 and IL-6 [42,43]. PGI 2 has also been demonstrated to reduce lipopolysaccharide-induced cytokine production in leukocytes through the inhibition of nuclear factor-kB [44].…”
supporting
confidence: 62%
“…2/2 mice, as previously described (34) and detailed in the online supplement. Purified CD4 1 cells were positively selected and then polarized down the T helper (Th) type 0, Th1, Th2, or Th17 pathway, as previously described (35,36).…”
Section: T Cell Isolation and Polarizationmentioning
confidence: 99%
“…Bone marrow from WT and gp91phox 2/2 mice was harvested and then cultured for 8 days, as previously described (34) and detailed in the online supplement.…”
Section: Dendritic Cell Culturementioning
confidence: 99%
“…Indeed, studies performed by our laboratory and other investigators revealed that the COX product prostaglandin (PG) I 2 , which signals through the G protein-coupled receptor IP, was a critical inhibitor of the adaptive immune response in animal models of allergic lung inflammation (14)(15)(16)(17)(18)(19)(20). IP predominantly couples to a G s -type G protein, leading to an increase in cAMP (21).…”
mentioning
confidence: 99%